Kinerja Pembangunan Ekonomi Daerah Kabupaten Semarang - Eko Prasetyo (STIE Widya Manggala, 2009)
This study aims ti find out regional economic performance as measured from the level of regional economic growth and its contribution to the people. This study utilizes sectoral economic growth theory, using sectoral industry agriculture and tourism as its bases that locally known as Intanpari. The growth and performance of regional economic development of Semarang district are relatively better than those of other areas in Central Java Province. Such a condition is achieved due to the vast number of intensive labor industries existing in the region and its sufficient natural resources (sufficient resources base). The development strategy in Semarang district, which is based on regional potentials (Intanpari) and on industry as the leading sector, is considered as successful. The performance of the regional economic development in this regiom has considered to the prosperity level of its people with lower income gap distribution.